Research on the Clinical Efficacy of Integrated Traditional Chinese and Western Medicine in Fracture Rehabilitation after Surgery - LI, Feng; Jumuddin, Farra Aidah (Journal of Neonatal Surgery, 2025)
Fracture rehabilitation outcomes may improve by integrating Traditional Chinese Medicine (TCM) with Western orthopaedic care. This review examines recent clinical evidence (2019–2025) on combined TCM-Western postoperative rehabilitation for fractures. A systematic search of English and Chinese literature identified ≥40 peer-reviewed studies, including randomized trials, cohort studies, and meta-analyses. Findings consistently show that integrative approaches can accelerate fracture healing, enhance functional recovery, and reduce complications compared to standard care alone. For example, meta-analysis evidence indicates significantly shorter healing times (by ~20–30%) and higher early union rates with adjuvant Chinese therapies. Integrative interventions (e.g. acupuncture, herbal medicine, tui-na massage) were associated with better pain relief and joint function scores, enabling earlier mobilization. Postoperative complication risks (infection, respiratory failure, etc.) also tended to be lower in integrative care groups. Mechanistically, TCM treatments may promote osteogenesis and mitigate inflammation (for instance, herbals like Epimedium suppress RANKL and activate Wnt signaling to stimulate bone formation). We conclude that an integrated TCM-Western model is a clinically efficacious and safe strategy for fracture postoperative rehabilitation, yielding faster recovery and holistic benefits.